Comparative effect of aerobic, bharathanatyam and kandyan dance on vo2 max. - Sabaananth, S.; Gopinath, V. (University of Malaya, Malaysia, 2013)
Introduction: Dance is an art form that generally refers to movement of the body, usually rhythmic and to music, used as a form of expression, social interaction or presented in a spiritual or performance setting. Purpose: The purpose of this study was to find out the comparative effect of Aerobic, Bharathanatyam and Kandyan dance on VO2 max. Methods: To achieve the purpose ninety (N=90) women dancers were selected from Jaffna, Sri Lanka, and their age were ranged between 17 and 18 years. They were classified in to Aerobic dance [(AD)( n=30], Bharathanatym Dancers [(BD) (n=30] and Kandyan Dancers [(KD)( n=30] and practice their respective dance training, 45-60 min / day / three days / week over the period of twelve weeks. VO2 max was assessed for all the selected subjects by Queen’s step test before and after the intervention programme, The pre-test and post test means of experimental groups I, II and III were tested for significance by applying dependent ‘t’ to find out the difference between pre and post test. After eliminating the influence of pre-test on post-test means of experimental groups the analysis of variance (ANOVA) was used to find out the mean gain differences. In addition to this, Scheffe’s post-hoc test was employed, if the F-ratio of the mean gain was significant. In all the cases 0.05 level of confidence was fixed to test the significance. Results: The result of the study on VO2 max indicates that there was a significant different among the Aerobic, Bharathanatyam and Kandyan Dancers. Conclusion: From the results it was concluded that there was a significant difference between Aerobic and Bharathanatyam, Aerobic and Kandyan Dance groups on VO2 max. However between Bharathanatyam dance and Kandyan dance insignificant difference was observed on VO2 max.
Keywords: Bharathanatyam; kandyan dance; VO2 max